Patient with a Starr-Edwards Prosthesis in the Aortic Position for 40 Years - Miranda, Matheus; Nascimento, Luciene do; Haddad, Michel Raineri; Haddad Junior, William Teixeira; Haddad, William Teixeira [UNESP]; Buffolo, Enio (I C R Publishers, 2013)
Herein is reported the case of a patient who presented initially with aortic insufficiency and a fistula between the sinus of Valsalva and right atrium when aged 31 years. Closure of the fistula and replacement of the aortic valve with a Starr-Edwards A-9 caged-ball prosthesis was performed in 1972, since when the valve has survived for 40 years without dysfunction. This is one of the longest follow ups of the Starr-Edwards prosthesis reported, and highlights the possibility of acceptable valve performance over long periods of time.